Mixed-copulas approach in examining the relationship between oil prices and ASEAN’s stock markets - Paravee Maneejuk (2018)
© 2018, Springer International Publishing AG. This study aims to examine the relationship between oil prices and stock markets in five ASEAN countries: Thailand, Indonesia, Malaysia, Singapore, and the Philippines. Copula approach is used for modelling dependence structure between variables. In essence, this study considers four classes of copula, namely Archimedean copulas, Elliptical copulas, extreme value copulas, and mixed copulas, to examine the dependency between oil prices and stock market prices. We found that Thai, Malaysian, and Indonesian stock markets are likely to boom when crude oil prices increase while the Singaporean stock market as well as the Philippines’s stock market tend to move in the opposite direction to crude oil prices. However, the results show that these relationships are not strong.